Acute interstitial nephritis: New agents for an old entity. Issue 3 (October 2020) - Cardoso, Filipa; Barata, Rui; Navarro, David; Mendes, Marco; Góis, Mário; Sousa, Helena; Nolasco, Fernando
A 73-year-old male diagnosed with metastasized malignant melanoma was started on combined therapy with dabrafenib and trametinib, but soon admitted with gastrointestinal intolerance. Blood tests revealed toxic hepatitis and acute kidney injury. Renal duplex Doppler ultrasound ruled out urinary and vascular obstruction and apart from a positive antinuclear antibody, other tests for acute kidney injury assessment were unremarkable. Urinary sediment microscopy showed dysmorphic red blood cells, in addition to yellow-pigmented casts. Kidney biopsy revealed signs of acute tubular necrosis and acute interstitial nephritis. Kidney function declined further, prompting the need for urgent hemodialysis. Treatment with dabrafenib and trametinib was stopped and corticosteroids were initiated, with a rapid beneficial effect on both the kidney function and liver toxicity. Hemodialysis was stopped after four sessions with a full recovery after 2 months of corticosteroids, with the dose being slowly tapered. Unfortunately, the patient died a few months later due to melanoma progression. Dual therapy with the combination of a B-Raf proto-oncogene inhibitor with a mitogen-activated protein kinase kinase inhibitor improves response rates and has been recently approved by the U.S. Food and Drug Administration, and while dermatologic toxicity is a common adverse effect, the association with acute renal failure has seldom been reported. To the best of our knowledge, there are only two published case reports of acute kidney injury in patients treated with combination of dabrafenib and trametinib and only one of them is biopsy proven. Further studies evaluating the incidence of acute kidney injury with the combination of B-Raf proto-oncogene and mitogen-activated protein kinase kinase inhibitors are warranted, and may provide new insights into the mechanisms underlying renal toxicity.